The effect of religiosity on organizational citizenship behavior and affective commitment: A case of Islamic higher education institution - Wiwik Yulistia Ningsih (Asian Journal of Islamic Management (AJIM), 2019)
Purpose: This study aims to analyze the effect of religiosity on organizational citizenship behavior and affective commitment at the Universitas Muhammadiyah Yogyakarta as an Islamic higher education institution.Design: Respondents of this study were 96 permanent faculty staffs. This study used questionnaire as data collection techniques. The data analysis method used is multiple linear regression with SPSS as an analysis tool.Findings: The results of this study indicate that religiosity has a significant positive effect on organizational citizenship behavior, religiosity has a significant positive effect on affective commitment and affective commitment has a significant positive effect on organizational citizenship behaviorOriginality/value: Studies related to organizational citizenship of Islamic institution are still limited.